2016
DOI: 10.18632/oncotarget.14244
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA GAS5 differentially regulates cell cycle arrest and apoptosis through activation of BRCA1 and p53 in human neuroblastoma

Abstract: The long non-coding RNA GAS5 has been shown to modulate cancer proliferation in numerous human cancer systems and has been correlated with successful patient outcome. Our examination of GAS5 in neuroblastoma has revealed robust expression in both MYCN-amplified and non-amplified cell lines. Knockdown of GAS5 In vitro resulted in defects in cell proliferation, apoptosis, and induced cell cycle arrest. Further analysis of GAS5 clones revealed multiple novel splice variants, two of which inversely modulated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 47 publications
(63 reference statements)
2
38
0
1
Order By: Relevance
“…GAS5 has been identified as a tumor suppressor, and its down‐regulation is related to both clinicopathological characteristics and patient prognosis in multiple cancers [Liu et al, ; Ma et al, ]. GAS5 suppresses tumorigenesis by down‐regulating miR‐23a expression in non‐small‐cell lung cancer [Mei et al, ] and gastric cancer [Liu et al, ], and it modulates cell cycle arrest and apoptosis through activation of BRCA1 and p53 in human neuroblastoma [Mazar et al, ]. GAS5 also exerts a tumor‐suppressive function by down‐regulating miR‐222 in human glioma [Zhao et al, ], and it acts as a molecular sponge to regulate miR‐103 and mediate the AKT/mTOR signaling pathway in prostate cancer [Xue et al, ] and PTEN expression in endometrial cancer [Guo et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 has been identified as a tumor suppressor, and its down‐regulation is related to both clinicopathological characteristics and patient prognosis in multiple cancers [Liu et al, ; Ma et al, ]. GAS5 suppresses tumorigenesis by down‐regulating miR‐23a expression in non‐small‐cell lung cancer [Mei et al, ] and gastric cancer [Liu et al, ], and it modulates cell cycle arrest and apoptosis through activation of BRCA1 and p53 in human neuroblastoma [Mazar et al, ]. GAS5 also exerts a tumor‐suppressive function by down‐regulating miR‐222 in human glioma [Zhao et al, ], and it acts as a molecular sponge to regulate miR‐103 and mediate the AKT/mTOR signaling pathway in prostate cancer [Xue et al, ] and PTEN expression in endometrial cancer [Guo et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that GAS5 could induce G0/G1 arrest in human neuroblastoma (Mazar, Rosado, Shelley, Marchica, & Westmoreland, ), colorectal cancer (Yang et al, ), and stomach cancer (Liu et al, ). In this study, we found that the percentage of cells in the G0/G1 phase was increased by GAS5 overexpression, but decreased by GAS5 silence, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…(growth arrest-specific 5) lncRNA acts as a tumor suppressor with various proposed mechanisms of action, including, cell cycle control Mazar et al 2016;Luo et al 2017), proliferation (Kino et al 2010;Li et al 2017b) and regulation of epithelial to mesenchymal transition (EMT) program (Zhuang et al 2015). Considering the multi-faceted mechanisms by which GAS5 functions as a tumor suppressor, it is plausible that its expression may be predictive of response to multiple drugs.…”
Section: Discussionmentioning
confidence: 99%